Find the Quadratic Constant of Variation 4x-2y=-6

Math
4x-2y=-6
Subtract 4x from both sides of the equation.
-2y=-6-4x
Divide each term by -2 and simplify.
Tap for more steps…
Divide each term in -2y=-6-4x by -2.
-2y-2=-6-2+-4x-2
Cancel the common factor of -2.
Tap for more steps…
Cancel the common factor.
-2y-2=-6-2+-4x-2
Divide y by 1.
y=-6-2+-4x-2
y=-6-2+-4x-2
Simplify each term.
Tap for more steps…
Divide -6 by -2.
y=3+-4x-2
Cancel the common factor of -4 and -2.
Tap for more steps…
Factor -2 out of -4x.
y=3+-2(2x)-2
Cancel the common factors.
Tap for more steps…
Factor -2 out of -2.
y=3+-2(2x)-2(1)
Cancel the common factor.
y=3+-2(2x)-2⋅1
Rewrite the expression.
y=3+2×1
Divide 2x by 1.
y=3+2x
y=3+2x
y=3+2x
y=3+2x
y=3+2x
The given equation y=3+2x can not be written as y=kx2, so y doesn’t vary directly with x2.
y doesn’t vary directly with x
Find the Quadratic Constant of Variation 4x-2y=-6

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top